The history of Bengal : from the first Mohammedan invasion until the virtual conquest of that country by the English, A.D. 1757. - Stewart, Charles, 1764-1837. ([Place of publication not identified] Theclassics Us, 2012)
The history of Bengal from the ninth century to the Battle of Plassey (1757), published in 1813
AAL
Keywords: Bengal (India) -- History